2020
DOI: 10.1007/s40544-019-0344-9
|View full text |Cite
|
Sign up to set email alerts
|

FTIR analysis and monitoring of used synthetic oils operated under similar driving conditions

Abstract: The processes of degradation of engine oils operated in passenger cars of a uniform fleet of 25 vehicles were analyzed for oxidation content using infrared (IR) spectroscopy. As part of the experiment, the changes in engine oils occurring during actual operation (under conditions which can be described as “harsh”, i.e., short distance driving, frequent starting of the engine, and extended engine idling) have been observed. An evaluation of the Fourier transform infrared spectroscopy (FTIR) spectrum of an engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…Interestingly, a study using a low-cost IR sensor operating in the range of 800-1100 nm demonstrated that the device could match oxidation degradation with an R 2 value as high as 0.8459 and had an R 2 value of 0.9139 when comparing their device to a commercially available UV-Vis-NIR spectrometer over a similar range [54]. Others have classified oxidation in the Mid-IR, approaching the NIR, with wavenumbers from 3600 -3700 cm −1 associated with antioxidant depletion [47]. Studies of engine oil oxidation using mid-infrared (Mid-IR) spectra have commonly looked at the carbonyl region of the spectrum (1670 cm −1 to 1800 cm −1 ).…”
Section: Comparison With Infrared Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a study using a low-cost IR sensor operating in the range of 800-1100 nm demonstrated that the device could match oxidation degradation with an R 2 value as high as 0.8459 and had an R 2 value of 0.9139 when comparing their device to a commercially available UV-Vis-NIR spectrometer over a similar range [54]. Others have classified oxidation in the Mid-IR, approaching the NIR, with wavenumbers from 3600 -3700 cm −1 associated with antioxidant depletion [47]. Studies of engine oil oxidation using mid-infrared (Mid-IR) spectra have commonly looked at the carbonyl region of the spectrum (1670 cm −1 to 1800 cm −1 ).…”
Section: Comparison With Infrared Spectramentioning
confidence: 99%
“…An established norm in oxidation analysis is the use of infrared spectroscopy that can yield a plethora of detailed information about oxidation, nitration, additive depletion, and water/coolant infiltration. However, recent research using FT-IR analysis on real-world oil degradation under usual driving conditions indicated that most degradation overtime was due to oxidation [47]. Suppose a relatively inexpensive, easy-to-use method that requires only a 1 µL sample can yield relatively easy to interpret oxidation results that are comparable to those obtained by FT-IR analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Незважаючи на наявність системи очищення, насичення продуктами зносу на молекулярному рівні призводить до прискорення деградації масла та зниження показників антифрикційних, миючих властивостей тощо [1][2][3][4].…”
Section: основний матеріал дослідженьunclassified
“…Understanding the degradation processes that occur in motor oil in operation is important with respect to meeting current and future requirements. Researchers are also studying motor oil degradation with a view to optimizing the replacement intervals [29][30][31] and setting up the maintenance systems [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%